Benefits, Constraints And Risks In Infrastructure Development Via Public-private Partnerships In Zambia - Ngoma, Sydney; Mundia, Muya; Kaliba, Chabota (Penerbit Universiti Sains Malaysia, 2014)
Zambia, like many other countries, has embraced public-private partnerships (PPPs) as a project delivery method. The country faces budgetary constraints, which has caused the maintenance and provision of new infrastructures to be a challenge. PPPs appear to create opportunities that stimulate investment in infrastructure development and economic growth. The goal of this study was to highlight the benefits, constraints and risks inherent in implementing PPP construction projects in Zambia. Using a questionnaire survey to collect data, the study identified the benefits and confirmed the prevalence of constraints and risks in the implementation of PPP construction projects in Zambia. The major benefits, constraints and risks were identified and ranked. There was agreement among survey respondents regarding the ranking of benefits, constraints and risks regarding construction projects in Zambia. Appropriate improvements to the regulatory framework were recommended for the PPP procurement approach to be successfully utilised and implemented in Zambia.